Antígona. A eterna sedução da filha de Édipo - Carlos Morais (Classica Digitalia: Mito e (Re)escrita, 2016)
This volume includes several texts about the myth of Antigone, its classical expression and modern and contemporary reception, in different cultural contexts (Portugal, Brazil, Spain, France and Italy).